Determination of HIV Tropism in Patients with Antiretroviral Therapy Failure in Arkhangelsk Region - Yu. V. Ostankova; V. S. Davydenko; A. N. Shchemelev; E. B. Zueva; P. A. Virolainen; Areg A. Totolyan (Проблемы особо опасных инфекций, 2022)
The aim of the study was to determine the tropism of the human immunodeficiency virus in patients with virological failure of antiretroviral therapy (ART) from the Arkhangelsk Region based on the analysis of the env gene V3 loop nucleotide sequence.Materials and methods. We used blood plasma samples obtained from 76 HIV-infected persons from the Arkhangelsk Region with virological failure of antiretroviral therapy. The nucleotide sequences of the HIV env gene C2-V3-C3 region were studied by PCR followed by sequencing. The genotype of the studied strains was determined based on the analysis of their phylogenetic relations with reference sequences from the international GenBank database, as well as using specialized programs. To predict viral tropism, the Garrido rule and the online bioinformatic tool Geno2Pheno[coreceptor] were used. The Geno2Pheno[coreceptor] algorithm, determines the false positive rate (FPR) based on the analysis of the env gene V3 loop nucleotide sequence. Results and discussion. Significantly lower representation of R5X4/X4-tropic HIV variants in long-term infected persons with subsubtype A6 virus compared to subtype B virus has been shown. For all FPR cut-off algorithms, a significant correlation between subtype and HIV tropism was observed (p=0.0014 and p=0.013 for FPR 10 % and FPR 20 %, respectively). While among subtype B strains, at least 57 % were identified as R5X4/X4-tropic variants (for an FPR of 10 %), including two strains classified as X4-tropic; among HIV subsubtype A6 even at an FPR of 20 %, the frequency of R5X4/X4-tropic samples only slightly exceeded 22 %. It can be assumed that the dynamics of changes in HIV tropism depends on the virus subtype. Significant differences in the distribution of amino acid residues of the V3 region sequences in the examined group between R5-tropic and R5X4/X4-tropic strains of subsubtype A6 for positions 18 (χ2=7.616, p=0.0058), 21 (χ2=7.281, p=0.007), 24 (χ2=5.587, p=0.0181), and 34 (χ2=5.144, p=0.0233) have been demonstrated. Among the R5X4/X4-tropic strains of the A6 subsubtype, amino acid substitutions were registered at positions 6, 19, 21, 26, 29, 30, which were not found in the R5-tropic A6 strains. The high occurrence frequency of a number of mutations previously described as presumably associated with resistance to maraviroc and similar drugs may indicate a natural polymorphism characteristic of the A6 subsubtype, which does not correlate with resistance to CCR5 co-receptor antagonists.